Positive and negative allosteric interactions on muscarinic receptors - Hejnová, L; Tucek, S; el-Fakahany, E E (European journal of pharmacology, 1995)
It was previously found that alcuronium increases the binding of [3H]methyl-N-scopolamine to cardiac muscarinic receptors by a positive allosteric action while its effect on the binding of [3H]quinuclidinyl benzilate is negative. The, features of the antagonist's molecule which decide whether its allosteric interaction with alcuronium is positive or negative are not known. In the present work, it was found that alcuronium has a positive allosteric effect also on the binding of [3H]atropine and [3H]methyl-N-piperidinyl benzilate to muscarinic receptors in rat heart atria and that its effect on the binding of [3H]methyl-N-quinuclidinyl benzilate is negative. A comparison of the five radiolabelled antagonists that have been investigated so far indicates that the type of allosteric interaction (positive or negative) is not determined by the presence or absence of the quaternary nitrogen or of the benzilyl moiety in the molecule of the antagonist. Apparently, features of the N-bearing moiety of muscarinic antagonists other than the presence of a charge on nitrogen play a key role in the determination of the type of interaction.
Keywords: benziláty; techniky in vitro; Quinuclidinyl Benzilate; krysa rodu Rattus; Alcuronium; receptory muskarinové; chinuklidinylbenzilát; zvířata; antagonisté muskarinových receptorů; potkani Wistar; Piperidines; Benzilates; alkuronium; Rats, Wistar; Male; Atropine; atropin; alosterická regulace; In Vitro Techniques; Rats; Receptors, Muscarinic; myokard; piperidiny; Animals; Myocardium; mužské pohlaví; Allosteric Regulation; Muscarinic Antagonists